2011
DOI: 10.1186/1756-0500-4-307
|View full text |Cite
|
Sign up to set email alerts
|

Are old running shoes detrimental to your feet? A pedobarographic study

Abstract: BackgroundFootwear characteristics have been implicated in fatigue and foot pain. The recommended time for changing running shoes is every 500 miles. The aim of our study was to assess and compare plantar peak pressures and pressure time integrals in new and old running shoes.FindingsThis was a prospective study involving 11 healthy female volunteers with no previous foot and ankle problems. New running shoes were provided to the participants. Plantar pressures were measured using the Novel Pedar system while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A number of studies have shown that the characteristics of running shoes influence external impact forces and kinematics of runners. First, plantar pressure measures in runners using new and old running shoes showed that newer shoes have higher peak pressures than older shoes, suggesting a higher risk of injury to the foot and ankle when running shoes are used for shorter periods (Rethnam & Makwana, ). Thus, the authors recommended breaking into new running shoes slowly, using them for mild physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown that the characteristics of running shoes influence external impact forces and kinematics of runners. First, plantar pressure measures in runners using new and old running shoes showed that newer shoes have higher peak pressures than older shoes, suggesting a higher risk of injury to the foot and ankle when running shoes are used for shorter periods (Rethnam & Makwana, ). Thus, the authors recommended breaking into new running shoes slowly, using them for mild physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Few epidemiological studies have focused on the impact of running shoes on injury incidence (Theisen et al., ). While some studies have shown the influence of shoe characteristics on running pattern (Wakeling et al., ; Kong et al., ; Lieberman et al., ; Rethnam & Makwana, ; Bonacci et al., ), the causal relationship between running pattern and RRI has not been established. This prospective cohort study showed that runners using concomitantly more than one pair of shoes had a lower risk of RRI.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In several biomechanical studies, kinetics has been demonstrated to change with differences in shoe properties. Peak ground reaction force is increased by a reduction of normal pronation (Perry & Lafortune, 1995), harder midsole (Baltich, Maurer, & Nigg, 2015), changing to new shoes (Rethnam & Makwana, 2011) and using racing flats although not significant (Logan, Hunter, Hopkins, Feland, & Parcel, 2010). In addition, the peak vertical impact peak is reduced by smaller heelto-toe drop shoes (da Silva Azevedo et al, 2016), conventional running shoes (Logan et al, 2010) and 3 months of adaptation to smaller heel-to-toe drop (Giandolini, Horvais, Farges, Samozino, & Morin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the peak vertical impact peak is reduced by smaller heelto-toe drop shoes (da Silva Azevedo et al, 2016), conventional running shoes (Logan et al, 2010) and 3 months of adaptation to smaller heel-to-toe drop (Giandolini, Horvais, Farges, Samozino, & Morin, 2013). Moreover, the loading rate is increased by a reduction of normal pronation (Perry & Lafortune, 1995), changing to new shoes (Rethnam & Makwana, 2011), increasing heel-to-toe drop in shoes during overground running (Chambon, Delattre, Gueguen, Berton, & Rao, 2015) and using racing flats although only significant for men (Logan et al, 2010). Finally, knee flexion moment during push-off phase is reduced by smaller heel-to-toe drop shoes (Besson, Morio, & Rossi, 2017) while ankle flexion moment is increased by smaller heel-to-toe drop shoes (Besson et al, 2017) and by shoes with a rounded sole in the longitudinal axis (Boyer & Andriacchi, 2009).…”
Section: Introductionmentioning
confidence: 99%